2018
DOI: 10.1021/acs.biochem.8b00262
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Consequences of Mutation of Tryptophan 215 in Thrombin

Abstract: Thrombin normally cleaves fibrinogen to promote coagulation; however, binding of thrombomodulin to thrombin switches the specificity of thrombin toward protein C, triggering the anticoagulation pathway. The W215A thrombin mutant was reported to have decreased activity toward fibrinogen without significant loss of activity toward protein C. To understand how mutation of Trp215 may alter thrombin specificity, hydrogen-deuterium exchange experiments (HDXMS), accelerated molecular dynamics (AMD) simulations, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 39 publications
2
31
0
Order By: Relevance
“…7 B ). Encountering such a characteristic decision plot and structural distribution when using experimental data would motivate the use of enhanced-sampling methods to improve the reference pool of structures ( 62 , 63 , 64 , 65 ).
Figure 7 Detection of critically insufficient conformational sampling in the input ensemble to be reweighted.
…”
Section: Resultsmentioning
confidence: 99%
“…7 B ). Encountering such a characteristic decision plot and structural distribution when using experimental data would motivate the use of enhanced-sampling methods to improve the reference pool of structures ( 62 , 63 , 64 , 65 ).
Figure 7 Detection of critically insufficient conformational sampling in the input ensemble to be reweighted.
…”
Section: Resultsmentioning
confidence: 99%
“…Pozzi et al 30 proposed the electrostatics at the W215−E217 segment as key factor, since mutations that stabilize the E* form predominantly lower the negative charge. Peacock et al 31 focused specifically on effects caused by mutations of the residues W215 and F227. Using activity assays, hydrogen-deuterium exchange experiments and accelerated MD simulations, they found that the π-stacking interactions between the two residues are essential to maintain an optimally active conformation.…”
mentioning
confidence: 99%
“…The HDXMS data showed that the W215A mutant had increased dynamics in the 170s CT loop, the 220s CT loop, and the N-terminus of the heavy chain (Fig. 1) (15). The AMD simulations predicted increases in dynamics in the same regions of the protein as were observed to exchange more in the HDXMS experiments.…”
Section: Introductionmentioning
confidence: 79%